Foundations of image science - Barrett, Harrison H; Myers, Kyle J (Wiley-Interscience, 2004)
Presents the mathematical underpinnings of image science at an accessible level. * The author is a preeminent researcher in the field and the past editor of the Journal of the Optical Society of America. * This is the first book to present material with a well defined theoretical and experimental basis.
Wiley series in pure and applied optics
Keywords: Image Interpretation, Computer-Assisted; interpretace obrazu počítačem; lékařská informatika